Impact of the crisis on industrial relations (Luxembourg, 2013)
"This report explores the impact of the crisis on industrial relations in the 27 EU Member States plus Norway. Looking first at industrial relations actors, it finds evidence of restructuring of the social partners and trade union mergers, and in some cases more visibility of the social partners, particularly trade unions. In terms of industrial relations processes, it finds evidence of an accelerating trend towards decentralisation of collective bargaining, a greater use of opening clauses and an increased level of industrial action. The main impacts on industrial relations outcomes have included a drop in the overall volume of bargaining, an increase in the number of agreements not being renewed, and a trend towards shorter agreements. There is also much evidence of pay pauses, pay freezes, pay cuts and working time reductions. The social partners have diverging views on many aspects of dealing with the crisis, although there is evidence in many countries of the social partners working together well in order to find common solutions."